Avaliação ecotoxicológica do antibiótico amoxicilina considerando sua presença no ambiente aquático - Brito, Lara Barroso (2016)
Pharmaceuticals can be introduced directly into the environmental by household disposal or pharmaceutical industry waste and indirectly through the excretion of humans and animals. Antibiotics are considered emerging contaminants because they are typically present at very low levels in the environmental and their human or ecological health effects are unclear. β-lactams represent more than 70% of antibiotics consumed in Brazil. Thus, in this context, this work evaluated the environmental impact of antibiotic amoxicillin (AMX) in different organisms, considering its presence in water. For that, we used the phytotoxicity test with seeds of tomato (Lycopersicon esculentum), cucumber (Cucumis sativus) and lettuce (Lactuca sativa), brine shrimp toxicity assay (Artemia salina), and embryo-larval toxicity test zebrafish (D. rerio), considering the lethal and sublethal effects and biomarkers determinations. AMX showed no toxicity to seeds of tomato, cucumber and lettuce in relation to seed germination and root elongation endpoints. For microcrustacean A. salina, AMX did not induce significant mortality after 24 h and 48 h exposure (LC50 > 100 mg/L) and it was classified as non-toxic (not categorized) according to the Globally Harmonized System (GHS). AMX also did not cause significant mortality in embryos and larvae zebrafish during 168 h of exposure. It had no significant effect on embryos hatching and larvae equilibrium. However, AMX significantly increased the larvae size at 6.25, 12.5 and 25 mg/L. Catalase (CAT), glutathione S-transferase (GST) and lactate dehydrogenase (LDH) activities in embryos and larvae of zebrafish were inhibited at 12.5 mg/L of AMX, 6.25, 12.5, 25, 50 and 100 mg/L of AMX and 1.5, 3.0, 6.25 and 12.5 mg/L of AMX, respectively. Therefore, AMX showed no significant acute toxicity to tested organisms, but it induced sublethal effects on larvae zebrafish in concentrations greater than those found in the aquatic environment, indicating that long-term chronic exposures must be investigated.